Upregulation of PD-L1 by EGFR Activation Mediates the Immune Escape in EGFR-Driven NSCLC. Issue 6 (June 2015) - Chen, Nan; Fang, Wenfeng; Zhan, Jianhua; Hong, Shaodong; Tang, Yanna; Kang, Shiyang; Zhang, Yaxiong; He, Xiaobo; Zhou, Ting; Qin, Tao; Huang, Yan; Yi, Xianping; et al.
<x xml:space="preserve">Abstract</x> Introduction: Epidermal growth factor receptor (EGFR) mutation status was reported to be associated with programmed death-ligand 1 (PD-L1) expression. However, the molecular mechanism of PD-L1 regulation by EGFR activation and the potential clinical significance of blocking PD-1/PD-L1 in EGFR-mutant non–small-cell lung cancer (NSCLC) treated with EGFR tyrosine kinase inhibitors (TKIs) were largely unknown. Methods: Western blot, real-time polymerase chain reaction, immunofluorescence, and flow cytometry were employed to explore the association between PD-L1 and EGFR activation. Then, we used EGFR-TKIs and downstream pathways inhibitors to clarify the detailed signaling pathway involved in PD-L1 regulation. Cell apoptosis, viability, and enzyme-linked immunosorbent assay test were used to study the immune suppression by EGFR activation and immune reactivation by EGFR-TKIs and/or PD-1 blocking in tumor cells and human peripheral blood mononuclear cells coculture system. Results: We found that EGFR activation by EGF stimulation, exon-19 deletions, and L858R mutation could induce PD-L1 expression. EGFR activation upregulated PD-L1 through p-ERK1/2/p-c-Jun but not through p-AKT/p-S6 pathway. PD-L1 mediated by EGFR activation could induce the apoptosis of T cells through PD-L1/PD-1 axis in tumor cells and peripheral blood mononuclear cells coculture system. Inhibiting EGFR by EGFR-TKIs could free the inhibition of T cells and enhance the production of interferon-γ. Synergistic tumor cell killing effects were not observed with EGFR-TKIs and anti-PD-1 antibody combination treatment in coculture system. Conclusions: Our results imply that EGFR-TKIs could not only directly inhibit tumor cell viability but also indirectly enhance antitumor immunity through the downregulation of PD-L1. Anti-PD-1/PD-L1 antibodies could be an optional therapy for EGFR-TKI sensitive patients, especially for EGFR-TKIs resistant NSCLC patients with EGFR mutation. Combination of EGFR-TKIs and anti-PD-1/PD-L1 antibodies treatment in NSCLC is not supported by the current study but warrant more studies to move into clinical practice.